EKSPLORASI KOSAKATA MATEMATIS DALAM BUDAYA TAK KASAT MATA SUKU DAYAK BIDAYUH-SOMU DI DESA SEBUDUH KECEMATAN KEMBAYAN - Rayo, Kandida Maro; Sugiatno, Sugiatno; Hamdani, Hamdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Â AbstractThe learning process that students do not only can be in the classroom can also be done outside or in the environment where they live. The environment around the students is also not far from the culture. Education and culture is something that can not in everyday life, because culture is unity and unity, apply in every society and education is a necessity for every individual in society. Currently the 2013 curriculum used is a very deep learning environment. In the textbook used is still a lot of language that must be understood students. The use of everyday language, language use is often interpreted as being able to speak in that language. More seriously here is defined as the ability to use symbols directly to communicate. The research used in this research is descriptive explorative research. The results obtained in this study are the mention of integers in the local language, the various units in the provision of ritual gear equipment, and the use of counting operations in the ritual activity of the device. all the results that can be integrated in mathematics learning.Keywords: Learning, Local Language, Etnomatematics